Qashqadaryo viloyatida qishloq turizmini rivojlantirish imkoniyatlari (SCIENCE and SOCIETY, 2026)
The article describes the opportunities for developing rural tourism in the Kashkadarya region from the perspective of district-level villages, mainly focusing on villages with high tourism potential located in rural districts, and reveals the current tourist potential of these villages.